Direct compensation of the spindle rotation error with an active hydrostatic journal bearing system. (March 2022) - Xu, Chunwang; Chen, Shujiang; Lu, Changhou; Wang, Kang; Sun, Jiaheng
Spindle rotation accuracy is important in machining process. Indirect compensation of spindle rotation error has been widely adopted in the field of machining accuracy improvement. However, there are some limitations on indirect compensation, and a little research on direct compensation can be found. This article utilizes active lubrication technology to improve the spindle rotation accuracy. Hydrostatic journal bearing with control recesses and servo valve drove by piezoelectric ceramics are adopted to compose the compensation element. The simple control strategy PID is adopted to provide control signal for servo valve. Both simulation and experiment are designed and conducted. The results show that proposed bearing system has the ability to improve the spindle rotation accuracy.